Perlindungan Hukum Bagi Notaris Pasar Modal dalam Melakukan Pendaftaran Ulang Surat Tanda Terdaftar Studi Putusan Nomor 38/G/2020/Ptun-Jkt - Pantouw, Regina Maryke Maria; Nefi, Arman (Wajah Hukum, 2025)
Notaries conducting activities in the Capital Market must first be registered with the Financial Services Authority (OJK) or have a Registered Certificate (STTD). Since the OJK Regulation Number 67/POJK.04/2017 of 2017 concerning Notaries Conducting Activities in the Capital Market was enacted, the Notary STTD has a validity period of 5 years and the Notary is required to re-register to comply with the POJK and re-register if the STTD has passed the validity period. In the case of Decision Number 38/G/2020/PTUN-JKT, Notary Y has performed the re-registration obligation as stipulated in POJK 67/2017, but OJK still issued a cancellation letter. This research discusses the legal protection given to Capital Market Notaries in re-registering STTD. The purpose of this study is to analyze the provisions of re-registration since the enactment of POJK 67/2017 and to find out the legal protection of Notaries who have re-registered their STTD. The method used in this research is doctrinal with the scope of STTD re-registration of Capital Market Notary. The materials used are primary, secondary, and tertiary legal materials. The place of research is Jakarta and the data collection technique is in the form of literature study which is analyzed qualitatively. The result of this research is a form of legal protection for Capital Market Notary related to STTD re-registration.